The first mitochondrial control region dataset: critically endangered freshwater turtles in Malaysia, Orlitia borneensis and Batagur borneoensis - Mohd Salleh, Mohd Hairul; Esa, Yuzine; Zainudin, Amir Asyraf Zainudina; Romli, Khairul Azhar; Wan Nawang, Wan Nur Fatin Syafiqah; Mohd Bakri, Athirah; Hussin, Nor Jasmin; Abdul Halim, Siti Amalia Aisyah (Penerbit UTM Press, 2023)
The Malaysian Giant Turtles and Painted Terrapin mitochondrial control region has the first data deposited to the GenBank database. This dataset describes phylogenetic tree relationships between the genera Orlitia and Batagur. Orlitia borneensis and Batagur borneoensis are freshwater turtles listed as critically endangered on the International Union for Conservation of Nature (IUCN) Red List and among 24 species of turtles in Malaysia. Since both species are critically endangered, the data provided here can be used for future conservation genetics studies in order to protect the species from being driven to extinction. A sample of each species was collected aseptically from adult O. borneensis (male) and B. borneoensis (female) in captivity at Bukit Paloh, Kuala Berang, Terengganu. The data for this study can be found in the GenBank database with accession numbers OQ571740 and OQ571740.